EFEKTIVITAS FEATURE KEMANUSIAAN SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN KEMAMPUAN MENULIS CERPEN KELAS X SMA NEGERI 2 BANTUL - Octavian Muning Sayekti (Universitas PGRI Semarang, 2015)
This research aims to find out the effectiveness of humanitarian feature learning media in enhancing the ability to write a short story class X SMAN 2 Bantul. Research design with a quasi-experimental wich design of a control group of non - equivalence. The sample in this research was 72 students, divided into experimental class ( X. IPA2 ) and the control class (X. IPA 4). The collection of data through tests that test writing short stories, questionnaires, and interviews. T-test calculation results showed that the scores t is greater than t table ( th = 4,804 > tt = 1,980 ) at the significance level of 5% with db 70. Shceffe test calculation results between groups using data posttest control group and the experimental group obtained F count ( F'h = 21.392 ) is greater than the F table ( F't = 3.985 ) with 70 db at significance level of 5 %. This suggests that learning to write short stories using learning media feature of humanity in the experimental group was more effective than learning to write short stories without using learning media feature of humanity in the control group. The questionnaire results showed that the majority of students, 55.5 % feel learning media feature given humanity, capable of inspiring them both in terms of appearance and structure of the short story ideas that include titles, conflict, character, setting, and problem resolution . The works of students who use the medium of learning in the form of human features appear to be more structured , both in terms of the appearance of ideas ranging from story ideas, titles, and logical thinking as well as the structure of the short story ( plot, setting, and characterization). Keywords: effectiveness , media feature of humanity , the ability to write short stories